21st century capitalism - Heilbroner, Robert (Norton, 1993)
Although communism lies shattered almost everywhere it once existed, no single form of capitalism has emerged worldwide. Which of the varieties of capitalism will be hardy enough to survive into the next century? Will the private sector make way for government to redress the failures of the market system? Does the defeat of the socialist vision portend that unbridled acquisitiveness will dominate the world? In tackling these questions, Heilbroner takes us to the roots of capitalist society. He views capitalism from a wide angle as both an economic system and a political order, showing the integral connections between the two that are often overlooked; finally, he addresses the overarching challenge ahead―a society that no longer believes in the inevitability of progress.